Schwann Cell Stimulation of Pancreatic Cancer Cells: A Proteomic Analysis - Ferdoushi, Aysha; Li, Xiang; Griffin, Nathan; Faulkner, Sam; Jamaluddin, M. Fairuz B.; Gao, Fangfang; Jiang, Chen Chen; van Helden, Dirk F.; Tanwar, Pradeep S.; Jobling, Phillip; Hondermarck, Hubert (Frontiers in Oncology, 2020)
Schwann cells (SCs), the glial component of peripheral nerves, have been identified as promoters of pancreatic cancer (PC) progression, but the molecular mechanisms are unclear. In the present study, we aimed to identify proteins released by SCs that could stimulate PC growth and invasion. Proteomic analysis of human primary SC secretome was performed using liquid chromatography–tandem mass spectrometry, and a total of 13,796 unique peptides corresponding to 1,470 individual proteins were identified. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment were conducted using the Database for Annotation, Visualization, and Integrated Discovery. Metabolic and cell–cell adhesion pathways showed the highest levels of enrichment, a finding in line with the supportive role of SCs in peripheral nerves. We identified seven SC-secreted proteins that were validated by western blot. The involvement of these SC-secreted proteins was further demonstrated by using blocking antibodies. PC cell proliferation and invasion induced by SC-conditioned media were decreased using blocking antibodies against the matrix metalloproteinase-2, cathepsin D, plasminogen activator inhibitor-1, and galectin-1. Blocking antibodies against the proteoglycan biglycan, galectin-3 binding protein, and tissue inhibitor of metalloproteinases-2 decreased only the proliferation but not the invasion of PC cells. Together, this study delineates the secretome of human SCs and identifies proteins that can stimulate PC cell growth and invasion and therefore constitute potential therapeutic targets.